The role of psychologists in the #FeesMustFall movement in South Africa: a thematic analysis - Kramer, Briony (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
Since 2015, students across South Africa have protested for free tertiary education. This protest movement is known as #FeesMustFall. It was deemed important to understand what psychologists could do in this movement, as these protests have highlighted the existing inequality and lack of transformation in South African universities. Further, these protests have shown to cause psychological sequelae, and, at present, there is very little information regarding the role of psychologists in these types of protests. In response, this current qualitative study explores what four psychologists believe their role could be within the protests, specifically within Grahamstown, Eastern Cape. Semi-structured interviews were conducted, and a Thematic Analysis methodology and Critical Psychology approach were used to analyse the findings. The results of the study revealed that these psychologists understood they could have varying roles within the protests. These varying roles linked to the broader concept of transformative versus ameliorative interventions. Ameliorative practices are usually more short-term in their effect to initiate change and are mainly aimed at the individual level, while transformative approaches are long-term and are mainly aimed at the societal level. Under the ameliorative approach, the psychologists' roles included that they provide individual therapy to students who were affected by the protests. The transformative approach, on the other hand, included that the psychologists use their role to act as advocates, negotiators or advisors, and therefore take an active role in assisting the University with the protests. The findings also showed that some participants were ambivalent and uncertain about their role. This ambivalence led to these participants questioning the protests themselves. Results also showed limiting factors within the Psychology profession, which prevented psychologists from taking a more active stance in the protests. The limiting factors referred to phenomena which prevent psychologists from being able to take a role, not only in protests, but in society as a whole. These factors included the idea of the psychologist being a bystander and/or being limited by the professional scope of practice. The implications of these findings highlight the possible key roles that psychologists can play in protest situations. However, it shows that perceived limiting factors sometimes prevent these roles from being fully realised. The findings also then point to a broader issue within the Psychology discipline, specifically relating to its relevance in the South African context.
Keywords: Higher education and state -- South Africa; Psychologists -- South Africa; Student movements -- South Africa; College students -- Psychology -- South Africa -- Makhanda; Student movements -- Psychological aspects